2019
DOI: 10.1002/cam4.2693
|View full text |Cite
|
Sign up to set email alerts
|

Phase III randomized, placebo‐controlled, double‐blind study of monosialotetrahexosylganglioside for the prevention of oxaliplatin‐induced peripheral neurotoxicity in stage II/III colorectal cancer

Abstract: BackgroundMonosialotetrahexosylganglioside (GM1) is a neuroprotective glycosphingolipid that repairs nerves. Oxaliplatin‐based chemotherapy is neurotoxic. This study assessed the efficacy of GM1 for preventing oxaliplatin‐induced peripheral neurotoxicity (OIPN) in colorectal cancer (CRC) patients receiving oxaliplatin‐based chemotherapy.MethodsIn total, 196 patients with stage II/III CRC undergoing adjuvant chemotherapy with mFOLFOX6 were randomly assigned to intravenous GM1 or a placebo. The primary endpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…In a clinical trial conducted in colon cancer patients on FOLFOX therapy (Table 2), GM1 attenuated symptoms of acute neuropathy (cold sensitivity, throat discomfort, muscle cramps), but its use to prevent the neurotoxicity of oxaliplatin is currently not recommended, and additional placebocontrolled studies are needed to better assess the utility of this agent in this clinical condition [4,67].…”
Section: Targeting the Inhibition Of Neuronal Apoptosis And Astrocytementioning
confidence: 99%
“…In a clinical trial conducted in colon cancer patients on FOLFOX therapy (Table 2), GM1 attenuated symptoms of acute neuropathy (cold sensitivity, throat discomfort, muscle cramps), but its use to prevent the neurotoxicity of oxaliplatin is currently not recommended, and additional placebocontrolled studies are needed to better assess the utility of this agent in this clinical condition [4,67].…”
Section: Targeting the Inhibition Of Neuronal Apoptosis And Astrocytementioning
confidence: 99%
“…No substantial differences in permanent discontinuation of chemotherapy and effects on survival were noted between GM1 and control. In a phase III randomized, placebo-controlled, double-blind study, there were no significant differences between the GM1 and control arms with regard to the prevention of chronic neurotoxicity based on all the evaluation endpoints in patients with CRC (14). Interestingly, the trial showed that patients in the GM1 group were less troubled by acute neuropathy, with fewer patients in the GM1 group than in the placebo group reporting cold sensitivity and muscle cramps in patients with breast cancer (15).…”
Section: Discussionmentioning
confidence: 99%
“…GM1 attenuated the symptoms of acute neuropathy in a clinical trial conducted in colon cancer patients treated with FOLFOX therapy; however, its use in preventing neurotoxicity of OHP is currently not recommended. The utility of this agent in this clinical condition requires additional placebo-controlled studies [ 198 ].…”
Section: Chemotherapy-induced Peripheral Neuropathy Prevention and Treatment: Therapy Candidates For Oipnmentioning
confidence: 99%